1776 N.J. Laws 26 - (:unkn) unknown (My University, 1777)
[A]ll able-bodied Men, not being Slaves ? between the Ages of sixteen and fifty Years ? and [] capable of bearing Arms" constituted the militia.
Keywords: MILITIAS